CONCEPTUAL STUDY OF SHUKRAVAHA SROTAS WITH ITS MULASTHANA - Debasis , Kundu (International Research Journal of Ayurveda & Yoga, 2020)
A healthy life with equally healthy and strong progeny has been the cherished wish of man since antiquity. It will be relevant to know now the basic concept of vajikarana and male infertility. The branch of Ayurveda which deals with management of defective semen and spermatogenesis along with sexual potencification is called vajikarana tantra. Of the two aspects of vajikarana procreation and recreation one or other has been receiving emphasis from time to time according to sociological condition. On the level of anatomical consideration of shukravaha srotas,Charak as well as Susruta and Vagbhata displays different views. Other authorities of Ayurveda have given no addition as new and the subject stands as controversial. Some of the commentator of ayurvedic classics like Chakrapanidatta and Dalahana have envisage different aspect of shukravaha sraotas. Some of which are specific in their outlook but detail description are not available. However the identification in the body which answers to the available description of shukravaha srotas should not be difficult and will not be out of place. Broadly speaking the nervous, the hormonal and the reproductive elements all three form the part of shukravaha srotas. Hence the study is under taken to understand the views of different acharays.